KEPRIBADIAN TOKOH UTAMA NOVEL NAMAKU LOUI(SA)KARYA ADYA PRAMUDITA: KAJIAN PSIKOANALISIS CARL GUSTAV JUNG - Hutabarat, Dame Kristina; Harrahap, Muharrina (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2023)
Multiple or intersexual sexes are born with characteristics that do not conform to the typical binary idea of ​​male or female. Lots of people don't know in more detail about this, but instead lots of people look down on people who have multiple or intersexual sex. As contained in the novel My Name is Louisa which tells of a female character named Louisa who has dual or intersexual sex, who grows and is raised by her mother, a single mother, so that her growth must always be in accordance with her own mother's wishes. This study aims to find out whether someone who has multiple sex or intersexuality faces discrimination given by society by using Carl Gutav Jung's psychoanalytic theory. The method used is descriptive qualitative which describes the observed data on the character's personality. The research uses observing and note-taking techniques. The research results obtained are as follows: 1) Louisa knows what factors cause her to experience intersexuality.